2013
DOI: 10.5455/2319-2003.ijbcp20130311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of honey on hepatotoxicity induced by antitubercular drugs in albino rats

Abstract: Background: Drug-induced hepatotoxicity is a potentially serious adverse effect of antituberculosis treatment (ATT) regimens containing isoniazid, rifampicin and pyrazinamide. Many in vitro and in vivo studies revealed that honey possess antioxidant property and hepotoprotective property but there is no systematic work available to test the effect of honey on antitubercular drugs induced hepatotoxicity in rats. Hence present study was carried out to explore the prophylactic and therapeutic effect of honey with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…On the other hand, the present histological study showed that of Nabk honey reduced the cellular changes induced by penicillin treated groups in both hepatoprotective and hepatocurative studies, indicating that Nabk honey contributed to the protection against penicillin induced liver toxicity. Our observations are highly supported by the other studies which suggest that Nabk honey exert their protective and curative effects against some drugs 59,66-(doxorubicin, penicillin, streptomycin, ibuprofen, acetaminophen and paracetamol)-induced hepatotoxicity 13,32,[56][57][58][59]66 . On hypothesis to explain the beneficial effects of honey in ameliorating biochemical parameters and histological changes is that honey may contains flavonoids, ascorbic acid, tocopherols, catalase and phenolic compounds.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…On the other hand, the present histological study showed that of Nabk honey reduced the cellular changes induced by penicillin treated groups in both hepatoprotective and hepatocurative studies, indicating that Nabk honey contributed to the protection against penicillin induced liver toxicity. Our observations are highly supported by the other studies which suggest that Nabk honey exert their protective and curative effects against some drugs 59,66-(doxorubicin, penicillin, streptomycin, ibuprofen, acetaminophen and paracetamol)-induced hepatotoxicity 13,32,[56][57][58][59]66 . On hypothesis to explain the beneficial effects of honey in ameliorating biochemical parameters and histological changes is that honey may contains flavonoids, ascorbic acid, tocopherols, catalase and phenolic compounds.…”
supporting
confidence: 77%
“…This might be the main reason for the restoration in the activities of the marker enzymes during administration of honey oxidative damage in a cell or tissue which occurs when the concentration of ROS (O 2 , H 2 O 2 and OH) generated exceeds the antioxidant capability of free radical scavenger 57 . Previous reports demonstrated that nabk honey has a protective role against many toxicants drugs 13,32,[56][57][58][59] . The present investigation clearly demonstrated that the injection of penicillin and antibiotics to guinea pigs have induced conspicuous alteration in the histological structure on the liver tissue in treated guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the distilled water treated group, a volume of distilled water equal to honey was given with gavage tube, while the honey-treated group was gavaged with honey at a dose of 2.5 g/kg two times daily, with a total of 5 g/kg/day [13]. A physiological saline (0.9% NaCl) in a similar dose of MTX (60 mg/Kg) interrupt the treatment at day four and administered intraperitoneally instead of MTX.…”
Section: Experimental Designmentioning
confidence: 99%
“…[8] Drug-induced hepatotoxicity is mediated through oxidative stress, lipid peroxidation, and antioxidant alteration. [9] Therefore, it is proposed that the agents which reduce the lipid peroxidation level in tissue and elevate in tracellular antioxidant defenses may have hepatoprotective effect in people taking antitubercular drugs. To solve this problem, use of silymarin is suggested in clinical practice.…”
Section: Original Articlementioning
confidence: 99%